Management of the internet shop conversion - Ащепкова, Наталья Сергеевна; Кулагин, Антон Дмитриевич (Technology audit and production reserves, 2016)
This article discusses the website modernization strategy: its design, number of areas for selling pages, presence of drop-down menu and prompts, design of selling pages, their colors, brightness, etc. The main aim of research is to develop methods for evaluating the effectiveness of different strategies for upgrading the website to increase sales and simulation of conversion control systems. Set of critical parameters that affect the sales growth is defined. To keep the interest of customers website design is periodically updated and modernized (new services in the form of "hot" keys, tips and on-line consultations are added). Selecting the modernization strategy should be carried out for efficiency reasons, optimizing the ratio "upgrade costs - increasing the number of sales." Modernization strategies for different segments of potential customers and the different product groups differ. This article discusses the most popular site modernization strategy: change in the number of areas for selling pages, change the color and size of areas for selling pages, add drop-down menu. The developed method allows predicting the change in the level of Internet shop sales for each of the three proposed strategies for upgrading the website. The authors estimated weighting factors of influence of changes in various areas to increase the conversion; analyzed the effectiveness of demand management systems, presented additional profit-capital ratio for improving the selling pages. The research results can be used by developers involved in the field of web design, as well as in the design of demand management systems.